Faunistic Survey of Insect-Pests Associated with Agaricus bisporus - Sharma, Anurag; Khanna, Anju Sudhakar; Raina, Rajeev; Kapoor, Renu; Thakur, Kehar Singh (International Journal of Economic Plants, 2019)
Present research conducted to acquaint with the insect pest fauna of commercially cultivated mushroom Agaricus bisporus revealed the abundance of insects belonging to orders Diptera and Coleoptera. In addition, spring tails and mites were also of common occurrence. Two genera of flies belonging to families Sciaridae and Phoridae registered their presence in these two mushrooms. Of these, the most prevalent grayish black small fly with filiform antennae, typical sciarid wings, long legs with contiguous coxae and elongated abdomen was identified as Sciara sp. (Diptera: Sciaridae). Though, this fly has been recorded from mushrooms from many mushroom growing nations of the world, it has been reported for the first time in Himachal Pradesh. Besides, Megaselia sp. (Diptera: Phoridae) was observed in two locations only. Incidence of four genera of beetles viz., Cyllodes indicus, Scaphisoma nigrofasciatum, Staphylinus sp. and Spondotriplax pallidipes was also recorded.